Comparative analysis of protein content of catfish (Clarias sp.) feed based on chicken waste and fish waste as high protein feed - Ananda Rifta Anastasya; Aulinisa Gita Herdiyanti; Nabila Khikmaturrosyida; Nurul Hudayah; Rindang Sike Nurindra Jati; Windi Rahmawati; Ajeng Daniarsih (Universitas Malikussaleh, 2026)
This study aims to analyze and compare the protein content of feed for catfish (Clarias sp.) formulated from chicken waste and fish waste as an alternative high-protein feed. The method used is descriptive quantitative by comparing the results of protein content analysis of two treatments, namely fish waste-based feed (PRO24) and chicken waste (PRO25). The feed was formulated with the same composition of additional ingredients, while the difference lies in the main protein source. Protein content analysis was carried out through laboratory testing using the Kjeldahl method. The results showed that the fish waste-based feed had a protein content of 62%, higher than the chicken waste-based feed at 57%. The 5% difference indicates the effect of the type of raw material on the protein content of the feed. Both types of feed still meet the optimal protein requirement standard for catfish growth. These results indicate that fish waste has more potential as an alternative protein source in feed formulations, but chicken waste can still be utilized with formulation improvements. Utilizing organic waste as a feed ingredient contributes to reducing production costs, as well as supporting the principle of sustainability through more efficient waste management. Keywords: Alternative Feed; Catfish; Chicken Waste; Feed Efficiency; Fish Waste